PENGARUH KINERJA GURU MATA PELAJARAN FIKIH TERHADAP HASIL BELAJAR SISWA DI MADRASAH ALIYAH MUHAMMADIYAH BANDAR - Setyawan, Agus; Wahyono, Catur (Institut Agama Islam Negeri (IAIN) Bone, 2024)
AbstractÂ This study aims to determine the effect of fiqh teacher performance on student learning outcomes at Madrasah Aliyah Muhammadiyah Bandar, This research is motivated by the existence of several teachers whose performance is still relatively low. Fiqh is one of the elements of religion that is furu'iyah (branch) which is obtained through reasoning or research. The main function of Fiqh lessons is to instill values and awareness of students' worship of Allah SWT. The type of research used in this research is quantitative research using the correlation method that connects the effect of teacher performance on the learning outcomes of the students it teaches. The results showed that the performance of the fiqh teacher was in the moderate performance category, while the student learning outcomes showed 91% of students in the moderate category, 3% in the high category and 6% in the low category, The results of the calculations in this study used simple linear regression analysis as well as from the results of the calculation there was an influence between the performance of the Jurisprudence teacher on student learning outcomes by 18.8% while 86.2% was influenced by other variables besides the teacher performance variable.